Pertumbuhan dan produksi tanaman sawi hijau (Brassica juncea L.) dan bawang daun (Allium fistulosum L.) pada pola tanam tumpang sari di tanah ultisol yang diberi pupuk organik cair urin kelinci - Nofrianil; Windyana (Fakultas Pertanian Universitas Majalengka, 2025)
This study aimed to evaluate the effect of the intercropping pattern of green mustard and spring onions given Liquid Organic Fertilizer (LOF) of rabbit urine on growth and production. The study used the experimental method with randomized Block Design (RBD). All treatments received fertilization with rabbit urine LOF at the same dose (50 ml/l water), and the treatments are P1 (monoculture of mustard greens), P2 (intercropping of mustard greens ₊ one row of spring onions), and P3 (intercropping of green mustard ₊ two rows of spring onions). Each treatment was repeated six times, so there were 18 treatment units. The growth and production components of green mustard and spring onions were the variables observed in this study. The data obtained were tested using Analysis of Variance (ANOVA) and further tested with the Duncan Multiple Range Test (DMRT). Furthermore, The effectiveness of planting patterns was evaluated using the Land Equity Ratio (LER) to compare land use efficiency with the economic benefits of the monoculture pattern. The results showed that the planting system with an intercropping pattern can increase (p<0.05) the growth and production of green mustard except for the variables of leaf length and root length (p>0.05). Meanwhile, the intercropping system of mustard greens, with both one row and two rows, provides higher land use efficiency than monocultures, with LER values of 2,132 and 3,334, respectively. It can be concluded that a planting system with an intercropping pattern between mustard greens and spring onions is an ideal and recommended combination.